Keselamatan Menurut Surat Efesus Pasal 2: 5,8-9 - Mandagi, Lamberty Y. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
This paper examines the subject of salvation based on the book of Ephesians chapter 2: 5,8-9. Why talk about the subject of salvation, because this subject is one of the most important points of the Christian faith and often causes fundamental differences among Christians because of the different interpretations of the biblical passages related to this subject, as well as differences in theology. Therefore the authors are interested in conducting research on this subject with a literature study approach, specifically thematic hermeneutics based on the Book of Ephesians as well as from the writings of experts. Through the literature research that has been done, it can be concluded that Salvation for believers is a gift from God and based on faith. Salvation is not a human effort but because of God's initiative in Jesus Christ. Therefore, believers must be grateful for God's work of salvation in Jesus Christ by doing various good deeds in response to Salvation as a very valuable gift from God for the people who believe in Him.